An Analysis of a White Preservice Teacher's Reflections on Race and Young Children Within an Urban School Context. (January 2016) - Jackson, Tambra O.; Bryan, Michelle L.; Larkin, Melissa L.
Building upon research that theorizes and documents students' perceptions of race, racial attitudes, and treatment by teachers, this article explores the impact of resegregation on how children of Color see and experience race in schools, specifically in relation to their teachers. Drawing upon our interpretations of a White preservice teacher's interactions with two African American elementary students, the students' awareness of her race, and their subsequent "racialized" perceptions of her effectiveness as a teacher, we explore the domino effects of racial and economic segregation on young children's schooling experiences, particularly as they relate to their relationships with teachers.